Latitude variations of soil bacterial community diversity and composition in three typical forests of temperate, northeastern of China - Fu, Xiao-Yu; Cheng, Zhi-Chao; Ni, Hong-Wei; Zhang, Rong-Tao (Frontiers in Earth Science, 2023)
Abstract: Soil bacteria are a crucial component of forest soil biodiversity and play important functions in numerous ecosystem processes. However, the differences of diversity and composition of soil bacteria with spatial, temporal and environmental gradients and the main drivers responsible for these differences remain to be studied in detail. We used Illumina MiSeq sequencing of bacterial 16S rRNA to investigate the distribution pattern and driving factors of bacterial diversity and composition in temperate forest soils at three different latitudes in northeast China, with samples taken at low, middle and high latitude. Each sample area was located at a distance of 1200 km. Our results indicate that the soil bacterial diversity decreased with increasing latitude. Members of the phyla Acidobacteria and Proteobacteria were the dominant in all investigated soils. Mean average temperature, soil pH and total nitrogen content were the key environmental factors shaping the soil bacterial diversity and composition in different latitudes of these temperate forests. This study revealed that the distribution of bacterial communities in temperate forests followed a latitudinal diversity pattern, which supplies an important reference value for the latitudinal pattern of soil biodiversity.